Nutritional Factors Related to Canine Gallbladder Diseases—A Scoping Review - Fabio Alves Teixeira; Kathleen Moira Aicher; Ricardo Duarte (Veterinary Sciences)
Gallbladder mucocele, cholelithiasis, choledocholithiasis, and cholecystitis are significant contributors to morbidity and mortality in dogs. The exact etiology of these conditions remains poorly understood, though various factors, such as endocrinopathies, dyslipidemia, and impaired gallbladder motility, have been suggested as potential contributors. Surgical intervention has been described as the first choice of treatment when biliary rupture or obstruction is suspected; however, medical management may be an important part of therapeutic or preventative strategy. Reports of medical management typically involve the use of a choleretic used to stimulate the flow of bile into the duodenum or substances that act as a “hepatoprotective” agent such as S-adenosylmethionine. In people, some nutrients appear to modify bile flow and are used as agents in the prevention and treatment of these conditions in the gallbladder. This paper provides a review of the literature about possible nutritional factors involved in the pathogenesis and treatment of canine gallbladder mucocele and cholelithiasis. Opportunities for the prevention and treatment of common biliary diseases in dogs may include the reduction of dietary fat, control of hyperlipidemia with omega-3 and fiber supplementation, ensuring an adequate supply of amino acids such as methionine and tryptophan, and the evaluation of vitamins such as vitamin D.